A new generalization on metric space and its metrizability. - Çeno , Stela; Subashi, Ledia (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
In this paper, our particular scope is to give a new generalization for the metric function and after that a proof of the metrizability of generalized φ-metric space. This new approach is influenced by the Chittenden’s metrization theorem.